(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2025)
The perennial herbs Mentha arvensis L. and Mentha spicata L., which are members of the Lamiaceae family, are extensively used in the nutraceutical, functional food, and pharmaceutical industries. Due to the potential presence of valuable secondary metabolites, a comparative study was performed on the essential oils (EOs) extracted from locally grown M. arvensis and M. spicata in Bangladesh to analyze their chemical constituents. The EOs were extracted from fresh herbs using the hydro-distillation method, and their chemical constituents were analyzed via gas chromatography-mass spectrometry (GC-MS). Carvone (59.58%) and limonene (31.14%) were recognized as the main constituents in the oil of M. arvensis, while carvone (55.03%) was also the principal constituent in the M. spicata EO. Additionally, significant proportions of dihydrocarveol (17.94%), dihydrocarveol acetate (7.69%), and limonene (6.9%) were detected among the twenty compounds analyzed in M. spicata oil. The key constituent found in these EOs may be responsible for the significant medicinal activities attributed to Mentha species. Bangladesh J. Sci. Ind. Res. 60(2), 125-130, 2025